Strategi Dinas Perindustrian Perdagangan Koperasi dan Usaha Kecil Menengah (Disperindagkop dan UKM) Kabupaten Kutai Barat Dalam Pengembangan Home Industri - Pestasius Darno (PREDIKSI : Jurnal Administrasi dan Kebijakan, 2020)
This research was conducted in Disperindagkop and UKM West Kutai Regency. This is because Disperindagkop and UKM are technically responsible for the growth and development of industrial homes in West Kutai regency. Researchers also conducted research in several home centers of the craft and small food industry in West Kutai Regency which is the object of Disperindagkop and UKM WestKutai Regency that must continue to be developed. Based on the results of research conducted by analyzing the data, information and explanations obtained, it can be concluded that the implementation of the industrial home development strategy in West Kutai Regency is based on the West Kutai Regency Regent Regulation No.2 of 2009 on the description of the main duties and functions of structural positions in Disperindagkop and SMEs of West Kutai Regency, then Disperindagkop and UKM of West Kutai Regency have the task of helping the Regent in carrying out  authority of the district government in the field of Industry, Trade, Cooperatives and SMEs based on the principle of autonomy and assistance duties. Included in the development of industrial home. In the application of home industry development strategy, there are supporting factors, namely and a good cooperation between Disperindagkop and UKM of West Kutai Regency with supporting parties such as agencies, banking institutions and other related practitioners, as well as harmonious relationships with small entrepreneurs. There are also inhibitory factors, such as internal inhibitor factors from Disperindagkop and UKM West Kutai Regency, namely the level of quality and quantity of the apparatus is still limited, the amount of budget funds for theUKM development program. As well as supporting facilities and infrastructure that are still inadequate. External inhibiting factors, namely the level of quality of human resources are still limited, lack of interest in self-entrepreneurship (no regeneration), high production prices while low purchasing power of the community, the creation of crafts and small food is still monotonous, and security conditions and political situations are not conducive.Penelitian ini dilakukan di Disperindagkop dan UKM Kabupaten Kutai Barat. Hal ini dikarenakan Disperindagkop dan UKM merupakan penanggungjawab teknis dalam pertumbuhan dan pengembangan home industri di kabupaten Kutai Barat. Peneliti juga melakukan penelitian di beberapa sentra-sentra home industry kerajinan dan makanan kecil di Kabupaten Kutai Barat yang merupakan objek dari Disperindagkop dan UKM KabupatenKutai Barat yang harus terus dikembangkan. Berdasarkan hasil penelitian yang dilakukan dengan menganalisa data- data, keterangan dan penjelasan yang diperoleh, dapat diambil kesimpulan bahwa pelaksana strategi pengembangan home industri di Kabupaten Kutai Barat adalah berdasarkan Peraturan Bupati Kabupaten Kutai Barat No.2 Tahun 2009 tentang uraian tugas pokok dan fungsi jabatan structural pada Disperindagkop dan UKM Kabupaten Kutai Barat, maka Disperindagkop dan UKM Kabupaten Kutai Barat memiliki tugas membantu Bupatidalam melaksanakan kewenangan pemerintah kabupaten di bidang Perindustrian, Perdagangan, Koperasi dan UKM berdasarkan azas otonomi dan tugas pembantuan. Termasuk dalam pengembangan home industri. Dalam penerapan strategi pengembangan home industri, terdapat factor pendukung yaitu dan jalinan kerjasama yang baik antara Disperindagkop dan UKM Kabupaten Kutai Barat dengan pihak pendukung seperti instansi, lembaga perbankan dan praktisi-praktisi lain yang terkait, serta hubungan yang harmonis dengan pengusaha kecil. Ada pula factor penghambat, seperti factor penghambat internal dari Disperindagkop dan UKM Kabupaten Kutai Barat yaitu tingkat kualitas dan kuantitas aparat masih terbatas, jumlah anggaran dana untuk program pengembanganUKM. Serta sarana dan prasarana penunjang yang masih kurang memadai. Faktor penghambat eksternal yaitu tingkat kualitas sumberdaya manusia masih terbatas, kurangnya minat berwiraswasta (tidak ada regenerasi), harga produksi yang tinggi sedangkan daya beli masyarakat rendah, hasil kreasi kerajinan dan makanan kecil masih monoton, serta kondisi keamanan dan situasi politik yang belum kondusif.